The Influence of Product Quality, Price, and Brand Image on Purchase Decisions for OMG Lip Cream Products - Dwi Puja Amelia; Samari; Rino Sardanto (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
The purpose of this study is to examine how brand image, price, and product quality affect students at Nusantara PGRI University in Kediri's decisions to buy OMG Lip Cream. The research focused on consumer behavior in the context of the growing marketing of local cosmetic products. The study employed a causal associative design and a quantitative method. A Likert-scale questionnaire was used to collect data from 40 active students in UNP Kediri's Faculty of Economics and Business who had at least once bought OMG Lip Cream. Multiple linear regression was employed in data analysis to ascertain the partial and simultaneous effects between variables. The results showed that product quality significantly influenced purchasing decisions. This confirms that product performance, brightness, and attractiveness are the main factors in determining consumer choice. Price was also shown to have a significant influence, indicating that affordability and product value are important considerations in the purchasing process. However, brand image did not have a significant influence, indicating that brand perception is not a primary determinant for consumers. At the same time, brand image, price, and product quality all had a big impact on buying decisions. In conclusion, brand image has less of an impact on purchase decisions than suitable price tactics and improved quality.